2021
DOI: 10.3390/ma14216489
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Intra- and Extra-Oral Scanning Technique for Transferring the Intaglio Surface of a Pontic of Provisional Restorations to Definitive Restorations

Abstract: When taking the final impression for a three-unit fixed partial denture (FPD), the intaglio surface of the pontic of provisional restoration cannot be transferred accurately to that of definitive restoration. The intra- and extra-oral scanning (IEOS) technique, a method for accurately reproducing the submucosal morphology of the superstructure of an implant, has been reported using an intraoral scanner. In the present study, we evaluated the difference between the conventional impression method using impressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(38 reference statements)
1
3
0
Order By: Relevance
“…Regarding the results of overall precision, the results accepted the null hypotheses, as there was statistically significant difference between the tested scanners, with IOS group showing better precision. As the result of the present study came in agreement with (Sanda et al, 2021) [21] , (Braian & Wennerberg, 2019) [2] . It is also came in agreement with (Gimenez-Gonzalez -2016.Pdf, n.d.) [7] who tested precision of TrueDef scanners.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding the results of overall precision, the results accepted the null hypotheses, as there was statistically significant difference between the tested scanners, with IOS group showing better precision. As the result of the present study came in agreement with (Sanda et al, 2021) [21] , (Braian & Wennerberg, 2019) [2] . It is also came in agreement with (Gimenez-Gonzalez -2016.Pdf, n.d.) [7] who tested precision of TrueDef scanners.…”
Section: Discussionsupporting
confidence: 93%
“…The 3D laser surface scanning technique has been used in a broad range of industries: assessment of residual stresses in the laser powder bed fusion of metals [17], improvement of the rolling contact joint of biomechanical implants [18], or the creation of three-unit fixed partial dentures [19]. In this study, this technique was applied to evaluate the sphericity of the soy balls using a coordinate measuring machine, NIKON Altera 10.10.8 (LK Metrology Ltd., Derby, UK), equipped with a non-contact NIKON LC15Dx laser scanning probe (Left panel, Figure 1).…”
Section: Measurement Of the Sphericity Of Soy Ballsmentioning
confidence: 99%
“…Over the past several decades, DITs using intraoral scanners have been considered an advantageous alternative to CITs because they improve comfort and are more efficient [8,9]. However, the accuracy of DITs remains inconclusive, and a wide range of values (5.38-810 µm) is documented [10].Most recent studies regarding the accuracy of implant impression techniques are limited to laboratory study designs [11][12][13][14][15][16][17], and only a few clinical studies have been reported [18]. As defined by ISO 5725-1, accuracy comprises trueness and precision.…”
mentioning
confidence: 99%
“…Over the past several decades, DITs using intraoral scanners have been considered an advantageous alternative to CITs because they improve comfort and are more efficient [8,9]. However, the accuracy of DITs remains inconclusive, and a wide range of values (5.38-810 µm) is documented [10].…”
mentioning
confidence: 99%